Hamka’s Exemplary Character: Nationalism Character Education - Saputro, Pradata Ardi; Miftahuddin, Miftahuddin (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This article contains the thoughts of nationalism from one of the figures in Indonesia, namely Haji Abdul Malik Karim Amrullah or Buya Hamka. Hamka is a thinker who is also a religious or scholar. The research used by researchers with five stages of historical research, namely selecting topics, heuristics, verification, interpretation, and historiography. In this article, the character education that Hamka received cannot be separated from religion. Character education according to Hamka is to develop the potential that exists in humans but does not extend from religious values. In the implementation of the existing curriculum, the role of Pancasila becomes dominant. Pancasila teaches a sense of responsibility towards the nation as well as biung based on religion. Nationalism becomes a student strength to become Indonesia's solid stronghold in the future.